PERAN AUDITOR INTERNAL DAN AUDITOR EKSTERNAL DALAM UPAYA PEMBERANTASAN KORUPSI DI INDONESIA - Rinjani (E-Jurnal Akuntansi TSM, 2022)
This study aims to examine how APIP as the government's internal auditor and BPK as the government's external auditor should carry out their roles and functions in an effort to eradicate corruption in Indonesia. This research is a qualitative research. Data collection was carried out using library techniques, namely by studying literature, articles, research journals, news from the media, and other documents containing information relevant to the research problem. The results of this study indicate that to increase the effectiveness of the APIP function as an internal audit in combating corruption and fraud in general, is through strengthening the internal audit organization and transforming the role of internal audit in terms of prevention, detection and investigation of fraud, especially corruption, which is supported by real commitment and support from senior management and other stakeholders who are willing to realize the vision, mission, and goals of the organization including developing an effective internal audit function. To be able to optimize their role in fighting corruption in Indonesia, in carrying out their duties BPK members must be great and professional people in conducting examinations, reporting indications of corruption to law enforcement officials (APH), having the courage to reveal the truth, having the ability to present professionally and quality, and able to be tested in court. BPK must also change the mindset about audit findings, which does not only focus on findings of compliance with laws and regulations, but must also focus on findings on the Internal Control System (SPI) which have the potential to have an impact on improving government governance and efforts corruption prevention. BPK must also begin to strengthen performance audits, which aim to test and assess economic, efficiency, and/or effectiveness aspects, as well as other performance aspects of a subject being examined, which results in recommendations that can lead to the achievement of Good Corporate Governance.